Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2196/31530
|View full text |Cite
|
Sign up to set email alerts
|

Digitally Supported Lifestyle Intervention to Prevent Type 2 Diabetes Through Healthy Habits: Secondary Analysis of Long-Term User Engagement Trajectories in a Randomized Controlled Trial

Abstract: Background Digital health interventions may offer a scalable way to prevent type 2 diabetes (T2D) with minimal burden on health care systems by providing early support for healthy behaviors among adults at increased risk for T2D. However, ensuring continued engagement with digital solutions is a challenge impacting the expected effectiveness. Objective We aimed to investigate the longitudinal usage patterns of a digital healthy habit formation intervent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(49 reference statements)
2
8
1
Order By: Relevance
“…About half of those who signed up found the messages helpful [ 33 ]. As opposed to our study findings, Lavikainen et al [ 34 ] found in their app-based study for T2DM prevention that older people were more likely to engage with the app [ 34 ]. The authors reported that only those who intensely interacted with the app achieved noteworthy changes in lifestyle-related risk factors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…About half of those who signed up found the messages helpful [ 33 ]. As opposed to our study findings, Lavikainen et al [ 34 ] found in their app-based study for T2DM prevention that older people were more likely to engage with the app [ 34 ]. The authors reported that only those who intensely interacted with the app achieved noteworthy changes in lifestyle-related risk factors.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors reported that only those who intensely interacted with the app achieved noteworthy changes in lifestyle-related risk factors. These active users were more likely to have already had a better diet, higher levels of physical activity, and lower stress levels at baseline [ 34 ]. Leung et al [ 35 ], in their study of an app-based intervention for T2DM risk, showed that app users who received a high risk of developing T2DM significantly improved their daily vegetable intake and physical activity over 2 years but not their smoking behavior or alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement with the NHS-DDPP in the present study follows a similar usage pattern seen in trials of digital diabetes prevention programmes, including patterns of attrition ( Harjumaa et al, 2020 ; Lavikainen et al, 2022 ) and the extent and duration of which users engage with different intervention features ( Block et al, 2015 ). Drawing direct comparisons with previous interventions studied in trials are somewhat problematic due to differences in intervention dosage.…”
Section: Discussionsupporting
confidence: 52%
“…Randomised controlled trials have assessed user engagement of digital behaviour change interventions to prevent T2DM over six ( Block et al, 2015 ; Harjumaa et al, 2020 ) and 12 months ( Lavikainen et al, 2022 ; Moin et al, 2018 ; Painter et al, 2020 ; Toro-Ramos et al, 2020 ; Sepah et al, 2017 ). Crucially, programme engagement was linked with reductions in fasting glucose and HbA1c ( Block et al, 2015 ), increased physical activity ( Batten et al, 2022 ), higher increase in diet quality ( Lavikainen et al, 2022 ) and decreased BMI or weight loss ( Lavikainen et al, 2022 ; Moin et al, 2018 ; Toro-Ramos et al, 2020 ; Sepah et al, 2017 ; Batten et al, 2022 ). One study analysed usage data from a digital programme designed to support self-management of T2DM, which was integrated into routine care in four Clinical Commissioning Groups in London, UK ( Poduval et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…No existing UK apps provide information on food suitability for PKU, and none have been validated by a healthcare organisation or certified by a recognised body. However, studies in other health and medical conditions have demonstrated that apps can improve adherence compared with traditional interventions, such as written educational information [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%